Analysis of Anticoagulant Therapy in the Elderly Patients, in Clinical Practice of Family Medicine Centers in the Kyrgyz Republic - S. M. Mamatov; B. Kanat kyzy; A. O. Musakeev; N. K. Kinderbaeva; T. J. Tagaev (Рациональная фармакотерапия в кардиологии)
Aim. To study the current state of the anticoagulant's prescription in elderly and senile patients with atrial fibrillation in the clinical practice of family medicine center, in the southern regions of the Kyrgyz Republic.Material and methods. Of the 1974 ambulatory medical observation cards, 470 patients with atrial fibrillation were selected who had indications for prescribing antithrombotic therapy (87 [18.5%] men and 383 [81.5%] women; 212 [45.1%] urban residents and 258 [54.9%] rural residents). The average age was 66.9±10.2 years. The analysis included data from 387 patients who received anticoagulant therapy. The frequency of prescribing antithrombotic therapy has been studied.Results. There were indications for anticoagulant therapy in 387 patients. Anticoagulants were taken by 167 (43.2%) patients, antiplatelet agents - 196 (50.6%), no therapy - 24 (6.2%). Anticoagulant therapy in 153 patients included warfarin, while only 11.8% had adequate INR control after one year of follow-up. Rivaroxaban was prescribed in 14 (8.4%) patients. 50% of patients had antiplatelet agents instead of anticoagulants, which were mainly prescribed by therapists of rural family medicine centers.Conclusion. In the southern regions of the republic, an unfavorable situation is observed with the prescription and management of elderly and senile patients on anticoagulant therapy. It is necessary to continue the research across the country in order to obtain a complete and real picture of the problem, and to develop a unified and relevant recommendation.